Identifikasi dan Mitigasi Risiko pada Proyek Konstruksi Menggunakan Metode House of Risk: Studi Kasus - Irawan, Heri Tri; Pamungkas, Iing; Hasnita, Hasnita; Fauza, Teuku Soleh (Jurnal Optimalisasi, 2024)
PT. Rigis Beukarya Property is a developer and contractor for housing projects in the West Aceh region. Housing projects that are implemented often experience obstacles in the construction of the project, such as over budget from the predetermined RAB, repeated repairs, materials that are ordered late, and exposure to bad weather which results in large losses due to these obstacles. The aim of this research is to identify risks in the Grand Keutapang housing development process, and mitigate the dominant risks in the Grand Keutapang housing development process. The House of risk (HOR) method is used to solve this problem by identifying risk events, risk agents and also designing risk agent mitigation strategies based on Aggregate Risk Potential (ARP) values. The results obtained from the house of risk stage 1 risk mapping show that there are 5 dominant risk agents that will be taken into consideration in developing mitigation actions, namely: A-14 (Lack of coordination between parties involved) with an ARP value of 3,384, A-1 (Incompetent/careful workforce) with an ARP value of 1,800, A-12 (Fluctuating company financial cash flow) with an ARP value of 826 , A-15 (Lack of supervision in the field) with an ARP value of 777, and A-8 (Increase in material prices) with an ARP value of 696. From the results of the house of risk phase 2 risk mapping, 5 risk mitigation action plans were obtained, including: PA-1 (Creating a monitoring and sanctions system) with an ETDk value of 5,961, PA-2 (Creating a standard diary (buhas)) with an ETDk value of 3,331, PA-3 (Creating a complete checklist) with an ETDk value of 6,236, PA - 4 (Making adaptive cost estimates) with an ETDk value of 4,270, and PA-5 (Improving the effectiveness of communication with all parties) with an ETDk value of 8.427.